Jejunoileal Atresia in a Newborn: Our Experience From Northern Tanzania and Literature Review. (February 2022) - Goodluck, Gregory; Gnanamuttupulle, Marianne; Sadiq, Adnan; Msuya, David; Chugulu, Samwel; Lodhia, Jay
Jenunoileal atresia is a congenital defect that causes small bowel obstruction in newborns. They are classified into 5 types and simple abdominal x-ray can aid in the diagnosis and with prompt resuscitation and surgery provides positive outcome. We present a 5-day-old newborn male baby was presented with features of intestinal obstruction since birth. Diagnosis of atresia of the small bowel was made through plain abdominal x-ray and was successfully operated. During the recovery, the baby developed surgical site infection which was managed promptly.